389 Combining transcriptomic- and tissue-based immune biomarkers to evaluate GB1275, a CD11b modulator, as a single agent or with pembrolizumab in patients with advanced solid tumors. (10th December 2020) - Messersmith, Wells; Rasco, Drew; Bono, Johann De; Wang-Gillam, Andrea; Park, Wungki; Nickle, David; Galkin, Anna; Ferguson, Beatrice; Carter, Laura; Zhou, Lei; Dupont, Jakob; Chaney, Marya; et al.
Abstract : Background: GB1275 is a first-in-class CD11b modulator in development as monotherapy and in combination with pembrolizumab or chemotherapy for the treatment of advanced solid tumors. Nonclinical data show that GB1275 reduced influx of tumor-associated myeloid-derived suppressor cells (MDSCs) and macrophages (TAMs), and repolarized M2 immuno-suppressive TAMs towards an M1 phenotype. We hypothesize that GB1275 administration can alleviate myeloid cell-mediated immunosuppressive effects and improve cancer treatment outcomes. A phase 1 trial evaluating GB1275 as monotherapy and in combination with pembrolizumab in specified advanced tumors in ongoing (NCT04060342 ). Methods: Blood gene expression variations as well as core tissue biopsies pre- and post-treatment were assessed following GB1275 monotherapy and combination with pembrolizumab. After obtaining informed consent, peripheral blood for MDSCs was collected from 21 patients pre- and two weeks post-treatment; core tissue biopsies were collected from 13 patients pre- and post-treatment. The frequency of MDSCs in whole blood was measured using the Serametrix MDSC FACS Assay. Gene expression transcriptome profiles were generated using NovaSeq platform. CD8 staining was performed at Neogenomics, and tumor infiltrating lymphocyte (TIL) quantification was performed by an independent pathologist. Results: Preliminary statistical analysis of MDSC immunophenotyping pre- and post- treatment is consistent with the proposed mechanism of GB1275, showing modulation of peripheral blood MDSCs in some patients. Preliminary gene expression analysis in the blood showed dose-dependent clusters following treatment with GB1275 alone. Moreover, the transcriptomic analysis revealed two unique expression patterns for patients treated with GB1275 monotherapy or in combination with pembrolizumab. Gene Set Enrichment Analysis showed that the CD11b pathway is downregulated in patients treated with GB1275. Analyses of TIL count revealed an increase in lymphocyte trafficking into the tumor after treatment with GB1275 alone or in combination with pembrolizumab. CD8 expression and transcriptomic analysis are underway and will be presented. Conclusions: GB1275 alone or in combination with pembrolizumab demonstrates biological activity, which may be dose dependent. The observed increase in TILs after treatment is supportive of the mechanism of action of GB1275. Further biomarker analyses in blood and tissues are ongoing and will be correlated with clinical activity in a larger number of patients. Ethics Approval: This ongoing study is being conducted in accordance with the the Declaration of Helsinki and Council for International Organizations of Medical Sciences (CIOMS) International Ethical Guidelines. The study was approved by the Ethics Boards of University of Colorado Hospital, Washington University School of Medicine - Siteman Cancer Center, Memorial Sloan Kettering Cancer Center, The Sarah Cannon Research Institute/Tennessee Oncology, South Texas Accelerated Research Therapeutics, and The Royal Marsden NHS Foundation Trust.